Identification of Polycyclic Aromatic Hydrocarbon and Heavy Metal in PM10 from Urban and Rural School Ambient (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Particulate matter (PM10) is a major pollutant of concern as it can be adsorbed with toxic substances like heavy metals and organic compounds like polycylic aromatic hydrocarbons (PAH). Automobile exhaust was among the most significant contributor towards the particulate matter problem in roadside areas of Malaysia. In addition, most of the school in Malaysia located  close to the roadside to ease accessibility that consequently further increase health risk among children. In this study, aerosol samples from school ambient in urban area (Kota Bharu) and rural area (Jeli) were analysed for PAH and concentration of heavy metal (Pb, Zn and C) identification. Result found the concentration of PM10 was higher in urban site than rural site with mean concentration Kota Bharu and Jeli is 52.57ug/m3 and 39.21 ug/m3 respectively. The 1- methylnaphthalene was the only PAH detected in both urban and rural areas. Result suggested that the concentration of lead (Pb) is the most prominent heavy metal measured in Jeli, while concentration of zinc (Zn) is the most significant of heavy metal in Kota Bharu.
Keywords: PM10; fluctuation; children risk; roadside school; automotive exhaust